234k views
0 votes
Jackson used the process of completing the square to solve the equation 2x2−12x=−6.

1 Answer

1 vote

Answer:


x=3-√(6),x=3+√(6)

Explanation:

we are given equation as


2x^2-12x=-6

Since, we have to solve it by using complete square

so, firstly we will complete square

and then we can solve for x

step-1:

Factor 2 from both sides


2(x^2-6x)=-3* 2

step-2:

Simplify it


x^2-6x=-3

step-3:

Add both sides 3^2


x^2-6x+3^2=-3+3^2

now, we can complete square


(x-3)^2=6

step-4:

Take sqrt both sides


(x-3)=-√(6),(x-3)=√(6)

step-5:

Add both sides by 3

we get


x=3-√(6),x=3+√(6)


User Astaroth
by
6.5k points